A stability theory for perturbed differential equations - Sheldon P. Gordon (International Journal of Mathematics and Mathematical Sciences)
The problem of determining the behavior of the solutions of a perturbed differential equation with respect to the solutions of the original unperturbed differential equation is studied. The general differential equation considered is X′=f(t,X) and the associated perturbed differential equation is Y′=f(t,Y)+g(t,Y).